Pengembangan Program Decision Support System Jurusan Teknik Mesin Universitas Jember - Aris Zainul Muttaqin (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Decision support system for mechanical engineering department is a program which is developed withDelphi-7. The program is able to compile data from Siakad Unej to become graphic display which attractive andinformative. The program is proofed able to support the accreditation team in searching and displaying thedepartment data fast and easily. For the future the program is still to develop to be an expert system.Keyword: decision support system